Activated coconut coir for removal of sodium and magnesium ions from saline water. Issue 47 (7th October 2016) - Hettiarachchi, Eshani; Perera, Rumali; Chandani Perera, A.D.L.; Kottegoda, Nilwala
Abstract: The potential of laboratory-prepared-activated coconut coir (ACC) for removal of Na + and Mg 2+ ions from saline water in desalination applications was studied. ACC was prepared by pyrolysis of raw coconut coir dust, treated with 50 wt% phosphoric acid. The ACC was characterized by Fourier transform infrared spectroscopy, powder X-ray diffraction, and scanning electron microscopy techniques while its BET surface area, methylene blue, and iodine values were measured to understand the surface characteristics. The laboratory-prepared-activated coir demonstrated a nanoporous structure with a BET surface area of 1, 235 m 2 g − 1 . The results further indicated the presence of oxygen containing functional groups in weak graphitic structure, while micro- to nanoporous nature was observed in ACC. Na + and Mg 2+ ion removal efficiencies from standard 0.200 mol dm − 3 NaCl and MgCl2 solutions were found to be approximately 50%. The results fit into Langmuir and Freundlich isotherms implying homogeneous monolayer coverage for both Na + and Mg 2+ adsorption. Optimized ACC dosage for removal of 40% of both cations from seawater was found to be 80.0 g L − 1 . ACC has the potential to remove up to 80% of Na + and 72% of Mg 2+ from seawater by repeated filtration. The acidic point zero charge of 5.5 ± 0.1 and the presence of nanopores explain the high cation adsorption characteristics compared to commercially available activated carbon. The used ACC was successfully regenerated by back washing with distilled water followed by pyrolysis.